Ecoregions of Baja California peninsula: A synthesis - Charlotte E. González-Abraham; Pedro P. Garcillán; Exequiel Ezcurra; Grupo de Trabajo de Ecorregiones Grupo de Trabajo de Ecorregiones (Botan‪ical Sciences, 2010)
The biological singularity of the Baja California peninsula has captured the attention of naturalists since long time ago. As result, a rich variety of ecological and biogeographical interpretations have been proposed. They share a common framework, but at the same time show disagreement. An exhaustive review of published literature was done to identify which ecoregions or transition zones show disagreement. We submitted the discordant transition zones to the analysis of regional experts during a workshop, and with the help of a geographical information system we generated decisions by consensus for the majority of discussed zones. Results are shown in a map of ecoregions of the Baja California peninsula, as a synthesis of the long time effort of study and analysis developed by individuals and institutions on the natural scenario of the Baja California peninsula.